Application of precooling stage in MR JT cryocoolers. (January 2022) - Rogala, Zbigniew
Highlights: The model of precooled MT JT cryocooler is developed. The effect of application of precooling stage in MR JT cryocooler is studied. Change of optimum MR composition due to precooling is investigated. Abstract: This paper investigates the effect of precooling stage application on steady-state performance of MR JT cryocooler. Modelling is carried out using modified approach for nonprecooled MR JT cryocoler employing Peng-Robinson EoS. This approach enables optimization of the MR composition for given precooling temperature. The research shows that the use of precooling significantly improves the performance of MR JT systems. In addition, it is investigated how precooling affects the optimum composition of MR. It has been also shown that precooling temperature can be optimized in terms of systems COP. This paper provides very clear insight on the effect and consequences of precooling application in MR JT systems.